Generalized vector quasi-variational-like inequalities. (8th February 2006) - Peng, Jian-Wen; Yang, Xin-Min
Abstract : Using maximal element theorem, we prove some existence theorems for the two types of generalized vector quasi-variational-like inequalities with non-monotonicity and non-compactness.